New Insights in Topical Drug Delivery for Skin Disorders: A Review - Saini, Madhurima; Garg, Dr. Shiv; Sharma, Dr. Piush; bhatt, Dr. Shailendra (Asian Journal of Pharmaceutical Research and Development, 2024)
Drug delivery systems are methods which are used to ensure that drugs get into the body and reach the area where they are needed. These systems must take a number of needs into account, ranging from ease of delivery to effectiveness of the drugs. The paper reviews an overview of a conventional and novel approach in the topical drug delivery system. Drug delivery via the skin is becoming progressively popular due to its convenience and affordability. The skin is the most important mechanical barrier to the penetration of many drug substances and acts as an ideal site to deliver the drug both locally and systemically. The topical route has been a favored route of drug administration over the last decades. Despite conventional topical drug delivery systems limits in poor retention and low bioavailability. To address some of the limitations posed by conventional dermatotherapy, nano-based technologies have been developed and have demonstrated a significant improvement in dermatotherapy. Their distinct physicochemical properties demonstrate their overall superior therapeutic efficacy in providing sustained and effective targeted drug release, as well as improved solubility of hydrophobic actives with optimized drug formulations. These nanocarriers are commonly classified as polymeric, lipid-based, metallic, and vesicular nanocarriers, including nanoemulsions, nanofibers, and microneedles.